2021
DOI: 10.3390/su13095318
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Measurement of the Interaction between the County Economy and Rural Transformation in Xinjiang, China

Abstract: Given the background of urbanization and rural revitalization in the new era, it is important to explore the synergy between regional macroeconomics and rural transformation, as a balanced and coordinated urban–rural relationship must be built to promote regional sustainable development and rural revitalization. This paper used the spatial econometric model to study the spatiotemporal synergy and interaction between Xinjiang’s county economy and rural transformation from 2007 to 2017. The conclusions were as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Network Diameter = max(All shortest paths between every pair of nodes) (9) where the shortest path here refers to the path in the network that has the least number of edges when traveling from one node to another [55]. 4 The average path length is the average value of the shortest path lengths between all the possible pairs of the nodes in a network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network Diameter = max(All shortest paths between every pair of nodes) (9) where the shortest path here refers to the path in the network that has the least number of edges when traveling from one node to another [55]. 4 The average path length is the average value of the shortest path lengths between all the possible pairs of the nodes in a network.…”
Section: Methodsmentioning
confidence: 99%
“…In rural China, the decreasing agricultural workforce due to urbanization and other factors poses challenges to straw resource supply [8]. Additionally, the weak industrial base in rural areas hinders the growth and development of companies focused on straw resource utilization [9]. Although the Chinese government is gradually promoting county-level pilot policies, these external stimuli do not adequately address the marketization challenges in straw resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al emphasized that focusing on the ruralization strategy is crucial for the future development of urbanrural relations in China, as it can effectively promote rural revitalization [28]. Tan et al argued that an in-depth exploration of the synergistic relationship between regional macroeconomics and rural transformation is critically important in promoting regional development [29]. Si pointed out that accelerating the process of urban-rural integration is an indispensable and critical link in realizing the rural revitalization strategy [30].…”
Section: County New Urbanization and Urban And Rural Developmentmentioning
confidence: 99%
“…Qiao G. et al (2023) analyzed the coupling coordination degree between rural revitalization and new urbanization, highlighting significant spatial disparities [19]. Tan B. et al (2021) identified spatial differences in the synergistic effect between county-level economic development and rural transformation in Xinjiang [20].…”
Section: Introductionmentioning
confidence: 99%